2012
DOI: 10.1017/s174392131300077x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular gas and dust in spiral galaxies

Abstract: Abstract. Several recent surveys (HERACLES, NGLS, KINGFISH, VNGS) have provided us with sensitive high-resolution observations of the molecular gas and dust content in spiral galaxies within 25 Mpc. I review recent results on the molecular gas content and its relation to star formation, as well as on the gas to dust ratio and the dust heating in spiral galaxies. I also present new results on the effect of environment on the molecular gas content of spiral galaxies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In particular, it is a cooling time of < 1 Gyr within 10 kpc that allows for the formation of molecular gas; this is the 'cooling time threshold' (Cavagnolo et al, 2008Rafferty et al, 2008Hogan et al, 2017 which has been observed to be a reasonably sharp cut-off in the presence of molecular gas in early-types and brightest cluster galaxies (BCGs). In early-types, it is only possible to get molecular gas if you are below this cooling time threshold -but in spiral galaxies molecular gas is present regardless (e.g., Wilson, 2013). This points to the conclusion that in early-types it is the simple condensation of the hot corona that gives rise to molecular gas, but in spiral galaxies such as the MW there is an additional mechanism occurring that does the job.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it is a cooling time of < 1 Gyr within 10 kpc that allows for the formation of molecular gas; this is the 'cooling time threshold' (Cavagnolo et al, 2008Rafferty et al, 2008Hogan et al, 2017 which has been observed to be a reasonably sharp cut-off in the presence of molecular gas in early-types and brightest cluster galaxies (BCGs). In early-types, it is only possible to get molecular gas if you are below this cooling time threshold -but in spiral galaxies molecular gas is present regardless (e.g., Wilson, 2013). This points to the conclusion that in early-types it is the simple condensation of the hot corona that gives rise to molecular gas, but in spiral galaxies such as the MW there is an additional mechanism occurring that does the job.…”
Section: Introductionmentioning
confidence: 99%